Comprehensive auditory discrimination profiles recorded with a fast parametric musical multi-feature mismatch negativity paradigm. Issue 4 (April 2016) - Vuust, Peter; Liikala, Lari; Näätänen, Risto; Brattico, Pauli; Brattico, Elvira
Highlights: MMNs to 16 out of 18 types of sound feature change (pitch, timbre, location, intensity, slide and rhythm) at three levels of magnitude are elicited even in the complex musical sounding stimuli. For pitch, intensity, location, and slide, the MMN amplitude increased with increasing magnitude of feature change. The MMN amplitude and latency to slide correlated with melody or rhythmic musical skills, respectively, even in musically untrained participants. Abstract: Objective: Mismatch negativity (MMN), a component of the auditory event-related potential (ERP) in response to auditory-expectancy violation, is sensitive to central auditory processing deficits associated with several clinical conditions and to auditory skills deriving from musical expertise. This sensitivity is more evident for stimuli integrated in complex sound contexts. This study tested whether increasing magnitudes of deviation (levels) entail increasing MMN amplitude (or decreasing latency), aiming to create a balanced version of the musical multi-feature paradigm towards measurement of extensive auditory discrimination profiles in auditory expertise or deficits. Methods: Using electroencephalography, we measured MMNs in healthy young adults to six types of sound feature change (pitch, timbre, location, intensity, slide and rhythm) at three different magnitudes of deviation, embedded in a music-sounding context. We also behaviourally assessed the individual musical aptitude using the Musical Ear Test (MET). Results: 16 of 18 sound feature changes elicited significant MMNs. For pitch, intensity, location, and slide, the MMN amplitude increased with increasing magnitude of feature change. We observed a ceiling effect for rhythm, and a floor effect for timbre. The slide MMN amplitude correlated positively with MET melody score and negatively with MET rhythm score. Conclusions: This novel paradigm provides an extensive, objective measure of auditory discrimination profile for different sound features embedded in a complex sound context. Significance: The paradigm can be adopted to study the neurophysiology of individuals with music processing difficulties or with special musical skills, and may be a useful tool for investigating development, plasticity, and deficits of auditory processing.